Brazil : Country Procurement Assessment Report - World Bank (Washington, DC, 2013)
This Country Procurement Assessment Report (CPAR) intends to contribute to a dialogue with the government, on its procurement policy and management agenda, by surveying the existing situation, assessing the situation in light of appropriate standards, indicating a meaningful array of issues that could be incorporated into the government's agenda, and examining the desirability, and workability of practices that would address those issues. It represents an effort by the Bank, to seek further ways to support the reform, and modernization of government procurement in Brazil. Notwithstanding the constraining environment imposed by the 1993 legislation, the country moved forward to modern practices, developing an Internet-based system to implement the electronic version of COMPRASNET, unanimously rated satisfactory. Nonetheless, the current legal framework lays no foundation for a dispute resolution system for government contracts, where exhaustively detailed legal provisions, discourage flexible interpretations, and allow the disqualification of proposals for reasons that are not substantial. In addition, there is lack of a normative entity, i.e., a policy-making agency responsible for developing procurement norms, and ensuring standardization of documents and procedures, thus leaving a gap in the procurement function, filled at times by the legal departments of the agencies, by the Federal Secretariat of Internal Control, and the Courts of Accounts, or by other law enforcement units, that are not specialized in government procurement. Recommendations include the establishment of a normative entity, the development of standard bidding documents, the introduction of Web-based planning, dispute resolution, and bulk buying, and, creating within the new procurement law, an effective dispute resolution system for contract implementation.